2016
DOI: 10.1136/bjsports-2015-095926
|View full text |Cite
|
Sign up to set email alerts
|

Training volume and soft tissue injury in professional and non-professional rugby union players: a systematic review

Abstract: A higher level of play may result in higher match injury incidence. Muscle and tendon injuries were the most common type of soft tissue injury, while the lower limb was the most common location of injury in rugby union players, and running was responsible for the highest injury incidence during non-contact events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Nevertheless, these were expert players at the maximum level of competition in Spain. Rugby Union is a team sport with high levels of injury ( Ball et al, 2017 ), especially at the maximum level ( Yeomans et al, 2018 ), therefore, completing the training protocol during six weeks continuously in the competitive season period with enough healthy players was already an important milestone achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these were expert players at the maximum level of competition in Spain. Rugby Union is a team sport with high levels of injury ( Ball et al, 2017 ), especially at the maximum level ( Yeomans et al, 2018 ), therefore, completing the training protocol during six weeks continuously in the competitive season period with enough healthy players was already an important milestone achieved.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Santos e Campos et al (2017) and Silva et al (2009) found that the use of bioceramic garments reduced pain both in patients with fibromyalgia and with post-polio syndrome. Performing physical activity can sometimes lead to the appearance of lesions, especially at high levels of performance (Alentorn-Geli et al , 2017; Ball et al , 2017). Thus, the use of such garments could also help reduce pain during the recovery phase of a sports injury.…”
Section: Discussionmentioning
confidence: 99%
“…Rugby union is an extremely high contact, physical sport and is the most popular collision sport worldwide (Brooks and Kemp, 2008). During rugby, the highest proportion of injuries occurs in the lower limb ranging from 41-55% with head and noncatastrophic injuries representing the second highest proportion at 12-33% of all injuries (Ball, Halaki and Orr, 2016). It consequently has one of the highest rates of injury of any sport with similar rates compared American Football, Australian Rules and Ice hockey (Lorentzon et al, 1988;Meyers and Barnhill 2004;Orchard, 2002).…”
Section: Introductionmentioning
confidence: 99%